Physical security layer with friendly jammer in half-duplex relaying networks over rayleigh fading channel: Intercept probability analysis - Phu Tran Tin; Duy Hung Ha; Minh Tran; Tran Thanh Trang (Institute of Advanced Engineering and Science, 2020)
In this research, thephysical security layer with a friendly jammerin half-duplex (HD) relaying networksover the Rayleigh fading channel is proposed and investigated. Firstly, we proposed the system model and the time switching,power splitting protocolsfor the system model. Then we conductedthe mathematical analysisfor deriving the exact analysis and asymptotic analysisintegral forms for intercept probability (IP). Finally, the analytical formulationis verified by the Monte Carlo simulation with all main system parameters. From the results, we can show that the simulation and analytical values are the same values.